A Study on Occupational Stress of Employees of Private Health Care Sector in Malappuram - M.Dhanabhakyam; Sarath.M (PT FORMOSA CENDEKIA GLOBAL, 2024)
Occupational stress is a growing concern that affects individuals and organizations alike. The impact of stress can be significant, leading to decreased job satisfaction, decreased productivity, increased absenteeism, and physical health problems. To address occupational stress, a combination of organizational, individual, and environmental interventions is necessary. The purpose of this study is to examine the extent and nature of occupational stress among employees in the healthcare sector, identify the factors contributing to it, and examine the change in stress across the various demographic factors. The researcher found a number of factors causing occupational stress, such as the inability to maintain work life balance, daily stressful challenges related to work, the emotional and psychological toll of the job, work dissatisfaction, etc. The researcher also found that stress levels vary according to gender, age, experience, and annual income